Toxicological effects of the chemical and green ZnO NPs on Cyprinus carpio L. observed under light and scanning electron microscopy. Issue 3 (15th October 2021) - Rasool, Saba; Faheem, Mehwish; Hanif, Uzma; Bahadur, Saraj; Taj, Sehrish; Liaqat, Fareeha; Pereira, Leonel; Liaqat, Iram; Shaheen, Shabnam; Shuaib, Muhammad; Gulzar, Sadia
Abstract: Nanoparticles in aquatic bodies cause serious harm to the aquatic organisms when accumulated in high amounts. However, green nanoparticles synthesized using plants can be less toxic as compared to chemical nanoparticles. Hence, we designed our study to investigate the toxicological effects of chemical and green zinc oxide nanoparticles (ZnO NPs) on the biological activity of juvenile Cyprinus carpio . The green ZnO NPs were synthesized from Solieria robusta, and chemical ZnO NPs were synthesized using zinc chloride solution and ammonium hydroxide. Characterization was done by using light microscopy, scanning electron microscope (SEM), Fourier transmission infrared radiation, and X‐ray diffraction (XRD) techniques. The highest absorbance of nanoparticles was observed at 360 which confirmed the synthesis of ZnO. The SEM analysis showed that green nanoparticles were hexagonal while the chemical nanoparticles were spherical to cubic in shape. Definite peaks were observed in XRD of green and chemical NPs at 2 θ angles 45.84° and 32.18°, respectively. Oxidative stress was determined by chemical analysis of catalase, glutathione S‐transferase (GST), glutathione (GSH), and lipid peroxidation (LPO) activities. The toxicological effects of chemical ZnO NPs on the catalase, LPO, GST, and GSH activities were more than green ZnO NPs. The histopathological investigation proved that the effect of chemical nanoparticles was worse than green ZnO NPs. More tissue damage was found in chemical nanoparticles than green synthesized nanoparticles. It was concluded that chemical nanoparticles can be replaced by green nanoparticles, as green nanoparticles are eco‐friendly with less toxicological effects. This replacement can limit the toxic effect of nanoparticles when they get accumulated in high amounts in water bodies. Abstract : Nanotechnology, that is, LM, SEM, FTIR, and XRD, detects harmful effects of nanoparticles on aquatic life. The effect of chemical and green ZnO NPs on the biological activity of juvenile Cyprinus carpio was analyzed. Green ZnO NPs were synthesized from a red alga Solieria robusta, and the characterization was done using LM, SEM, FTIR, and XRD analysis while the oxidative stress was determined by chemical analysis of catalase, GST, GSH, and LPO activities. The utilization of green‐synthesized ZnO NPs instead of chemical ZnO NPs decreases the damage caused by the excessive drainage of nanoparticles in aquatic bodies. Green ZnO NPs put less oxidative stress on the vital organs of fish as compared to chemical ZnO NPs.